2021
DOI: 10.3390/brainsci11091251
|View full text |Cite
|
Sign up to set email alerts
|

Has the Phase of the Menstrual Cycle Been Considered in Studies Investigating Pressure Pain Sensitivity in Migraine and Tension-Type Headache: A Scoping Review

Abstract: Objective: The aim of this scoping review was to identify if the phase of the menstrual cycle was considered in observational studies comparing pressure pain sensitivity between women with migraine or tension-type headache (TTH) and headache-free women. Methods: A systematic electronic literature search in PubMed, Medline, Web of Science, Scopus, and CINAHL databases was conducted. Observational studies including one or more groups with TTH and/or migraine comparing pressure pain thresholds (PPTs) were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 90 publications
(262 reference statements)
0
3
0
Order By: Relevance
“…Pain sensation is higher in the luteal phase than in the follicular phase and during menstruation. 23 According to molecular biology studies, decreased estrogen causes the hypothalamus to release norepinephrine, which triggers a drop in acetylcholine, dopamine, and serotonin, which can lead to premenstrual syndrome with common symptoms such as pain sensitivity, insomnia, fatigue, and depression. 24 The fact that the GABAergic system, which affects neuronal excitability, is associated with estrogen and progesterone levels that change during menstrual phases explains the change in perception of pain sensation during menstrual phases.…”
Section: Discussionmentioning
confidence: 99%
“…Pain sensation is higher in the luteal phase than in the follicular phase and during menstruation. 23 According to molecular biology studies, decreased estrogen causes the hypothalamus to release norepinephrine, which triggers a drop in acetylcholine, dopamine, and serotonin, which can lead to premenstrual syndrome with common symptoms such as pain sensitivity, insomnia, fatigue, and depression. 24 The fact that the GABAergic system, which affects neuronal excitability, is associated with estrogen and progesterone levels that change during menstrual phases explains the change in perception of pain sensation during menstrual phases.…”
Section: Discussionmentioning
confidence: 99%
“…Fixed-effects were included for four experimental factors that were all considered to be continuous variables: Headache intensity (scale from 0 (no pain) to 10 (extremely painful) score), state anxiety (scores from 20 to 80, with higher scores denoting greater anxiety) (26), sleep quality (scores from 1 to 4, with higher scores denoting worse sleep quality), and tolerance to stimuli over time (ranging from 1 to 27 days, with the latter being the end day). Anxiety (32,33), sleep quality (34,35), tolerance (36), menstruation (37,38) and medication intake (39) have been linked to the modulation of pain thresholds in past studies. Menstruation and medication intake were not included in the models as a result of a low number of observations in one condition.…”
Section: Methodsmentioning
confidence: 99%
“…Although all studies applied ICHD criteria, not all studies clearly reported the severity/frequency of migraine attacks and consecutiveness of patients. Third, the number of studies investigating PPT separately in women and men was limited and most studies did not control the menstrual phase in women, a topic recently discussed (46). Accordingly, current PPTs stratified by sex should be considered with caution.…”
Section: Strengths and Limitationsmentioning
confidence: 99%